2013
DOI: 10.1007/s00405-013-2426-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Italian nose obstruction symptom evaluation (I-NOSE) scale

Abstract: The NOSE scale is a questionnaire assessing QOL related with nasal obstruction. The aim of this study was to culturally adapt the NOSE scale into Italian (I-NOSE). Prospective instrument validation study. Cross-cultural adaptation and validation were accomplished. Cronbach α was used to test internal consistency in 116 patients complaining nasal obstruction and 232 asymptomatic subjects. Pearson and ICC tests were used for test-retest reliability analysis. Normative data were gathered from the 232 asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(93 citation statements)
references
References 25 publications
11
82
0
Order By: Relevance
“…We used a paired t-test to evaluate responsiveness by comparing the scores before and after surgical treatment. The NOSE scores before and after surgery were significantly different, which was similar to the results of previous studies (3)(4)(5)(6).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We used a paired t-test to evaluate responsiveness by comparing the scores before and after surgical treatment. The NOSE scores before and after surgery were significantly different, which was similar to the results of previous studies (3)(4)(5)(6).…”
Section: Discussionsupporting
confidence: 90%
“…The medical or surgical treatment of nasal obstruction is very common in rhinology practice (3)(4)(5)(6). The clinical diagnosis of nasal airway obstruction (NAO) is usually based on the patient's subjective feelings and the physician's assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies including the correlation of %PNIF and objective measurements, such as acoustic rhinomanometry and acoustic rhinometry, are necessary 1 . The NOSE scale is more frequently used in septal deviation assessment, in pre and posttreatment in adults 10,27,28 . Regarding the reliability of NOSE scale, the correlations found (NOSE versus rhinomanometry and NOSE versus VAS) were considered good for groups with and without obstruction and for individual measurements over time 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The NOSE scale is more frequently used in septal deviation assessment, in pre and posttreatment in adults 10,27,28 . Regarding the reliability of NOSE scale, the correlations found (NOSE versus rhinomanometry and NOSE versus VAS) were considered good for groups with and without obstruction and for individual measurements over time 27 . Another study in adults with nasal and mouth breathing has found a negative moderate correlation between NOSE and PNIF 16 .…”
Section: Discussionmentioning
confidence: 99%